Mathematical Modelling of Dengue Fever Spread with Education-Based Prevention in South Sulawesi - Pratama, Muhammad Isbar; Mariani, Mariani; Fadilah, Nur; Wahyuni, Maya Sari (Jurusan Matematika FMIPA UNM, 2025)
Dengue Fever (DF) remains a major public health challenge in many tropical regions, including South Sulawesi, Indonesia, where increasing case numbers highlight the urgent need for more effective disease control strategies. Traditional approaches that rely solely on medical treatment and vector suppression have shown limited long-term success, thus necessitating complementary preventive interventions such as health education. This study develops a deterministic SIRS host–vector mathematical model to analyse the epidemiological dynamics of DF transmission and to quantify the impact of educational intervention on reducing disease spread. The model incorporates human susceptibility, infection, temporary immunity, mosquito–human transmission mechanisms, and an education parameter that represents the rate at which susceptible individuals become effectively protected. Stability analysis is conducted to determine the conditions for disease persistence or elimination, and the basic reproduction number is derived using the next-generation matrix method. Numerical simulations are performed using biologically realistic parameter values for South Sulawesi. The results show that when , both human and vector infections converge to endemic equilibrium levels, consistent with the theoretical analysis. However, increasing the education-related protection parameter significantly reduces infection prevalence and can bring below unity, leading to disease eradication. The findings demonstrate that educational interventions play a critical role in reducing transmission intensity and complementing vector control measures. This study provides a mathematical foundation for evaluating community-based education as a sustainable component of DF prevention, offering valuable insights for public health policy in dengue-endemic regions.